Information please almanac 1993 : atlas & yearbook - 4 0 16; 5 (Boston : Houghton Mifflin, 1993)
Includes information on taxes, sports, daily living, celebrities, history, science, statistics, and world affairs.
Keywords: 2 -- 0; 6; Almanacs.;Almanacs.; United States;United States -- Statistics.;Statistics.; 2